Gerunds Found on the Scripts of “Thor” Movie - Alfira Akhlaqul Karimah (PGRI Provinsi Jawa Timur, 2021)
This research was aimed to analyze functions of the gerund found on the main character in the subtitle of “Thor” movie. Gerund is defined as the verb –ing functioning as a noun. This research was a kind of descriptive qualitative research viewed from the form of data. The main character of Thor movie, Thor Odinson, was the subject of this study. The instruments of this research were the researcher herself and the observation field note. All subtitle of Thor movie was the source of the data in this study. The data were the phrase (s) or sentence (s) containing the gerunds. In this research, there are some steps of data analysis namely: classification, description, and making conclusion. The researcher found three functions of gerund. Those functions were (1) gerund as subject consisting of 1 datum, (2) gerund as direct object consisting 11 data, and (3) gerund as subjective complement containing 23 data. It means that the researcher did not find a function of gerund called gerund as the object of preposition.